Rates of spectacle wear in early childhood in the Netherlands - Vasanthi Iyer; Clair A. Enthoven; Paula van Dommelen; Ashwin van Samkar; Johanna H. Groenewoud; Vincent V. W. Jaddoe; Sijmen A. Reijneveld; Caroline C. W. Klaver (BMC Pediatrics, 2022)
Abstract Background Refractive errors are relatively common all around the world. In particular, early onset myopia is associated with a significant burden in later life. Little is known about refractive errors in preschool children. The aim of this study was to assess the prevalence of spectacle wear, visual acuity and refractive errors in young Dutch children. Methods We analyzed data of three prospective population-based studies: 99,660 3- to 5-year-olds undergoing vision screening at preventive child healthcare organizations, 6934 6-year-olds from the Generation R study, and 2974 7-year-olds from the RAMSES study. Visual acuity was measured with Landolt-C or LEA charts, spectacle wear was assessed, and refractive errors at age 6 and 7 were measured with cycloplegic refraction. Results The prevalence of spectacle wear ranged from 1.5 to 11.8% between 3 to 7 years with no significant gender differences. Among children with spectacle wear at 6 years (N = 583) and 7 years (N = 350) 29.8 and 34.6% had myopia respectively, of which 21.1 and 21.6% combined with astigmatism; 19.6 and 6.8% had hyperopia, 37.2 and 11.1% hyperopia and astigmatism, and 12.5 and 32.7% astigmatism only. Conclusions Spectacle wear in European children starts early in preschool and increases to a relatively frequent visual aid at school age. Advocating early detection and monitoring of refraction errors is warranted in order to prevent visual morbidities later in life.